Masculinities in Literary Works on Indonesia's Post-Conflict Ambon Island - Udasmoro, Wening (Archīum Ateneo, 2024)
Various studies have examined masculinities within a sociological context, emphasizing linkage to violence, power, and militarization. In this sense, researchers have frequently positioned masculinities as the reproductions of male dominance and their perpetuations of conflicts and violence. No study has examined the roles that masculinities and their embedded values have played in building and maintaining peace. This article seeks to fill in the gap by examining how young people on Ambon Island helped create peace by expressing their fluid masculinities through literary works. This article focuses on poems by two Ambonese men—one a prominent peacebuilder and another a former combatant who later became involved in peacebuilding works. Critical Discourse Analysis (CDA) enabled an understanding of the ideology of the poems. With this method, wordings, alternative wordings, and rewordings served as the tools of analysis. Findings revealed that while masculinity of the traditional gender order is often associated with violence, courage, strength, and machismo, these writers from Ambon Island have presented fluid masculinities through their literary works as an instrument for creating sustainable peace.